2019
DOI: 10.5937/jaes17-22021
|View full text |Cite
|
Sign up to set email alerts
|

Validation of strength and flexibility of sengon (Paraserianthes falcataria) by experimental tree-pulling test and numerical simulation

Abstract: Stability assessment of trees is considered important in urban areas to detect possible occurrence of tree failures that often result in disastrous damages. Tree-pulling test is a low-cost, well-known method that has been practiced by researchers and practitioners alike from several decades ago. From the method, a number of parameters related to the physical characteristics of the tree can be further derived. However, the tree-pulling test has only been widely practiced mostly for tree species in subtropical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…[46] found that uniformly tapered stems (i.e., those of Cryptomeria japonica trees) subjected to wind and snow loads had breaks located between 50% and 70% of the tree's height, while In ref. [43] showed trunk break at 13.5% H. The distribution of stresses along the stem is influenced not only by the horizontal load considering the wind, but also by the moments applied considering the branches and by the horizontal components of the selfweight, which appear due to the deflection of the trunk. Furthermore, stresses are affected by diameter variation, which impacts the moment of inertia of the transversal section of the trunk.…”
Section: Normal Stressesmentioning
confidence: 97%
See 3 more Smart Citations
“…[46] found that uniformly tapered stems (i.e., those of Cryptomeria japonica trees) subjected to wind and snow loads had breaks located between 50% and 70% of the tree's height, while In ref. [43] showed trunk break at 13.5% H. The distribution of stresses along the stem is influenced not only by the horizontal load considering the wind, but also by the moments applied considering the branches and by the horizontal components of the selfweight, which appear due to the deflection of the trunk. Furthermore, stresses are affected by diameter variation, which impacts the moment of inertia of the transversal section of the trunk.…”
Section: Normal Stressesmentioning
confidence: 97%
“…Comparing deflection values using literature is complex because different authors use different measurement methodologies. Some of them consider only the inclination of the root plate [15,17], and others consider the inclination of the root plate and the deflection of the stem together [26,33,43], as in this study (Figure 2). Furthermore, the deflection is influenced by geometric tree parameters such as height, diameter, and taper [24], and also by mechanical properties of the trunk and root wood, as modulus of elasticity [15].…”
Section: Comparison With Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A dőlésveszély pontos meghatározására használható módszer, melyben az imitált szél erősségét és a törzs megdőlésének mértékét is rögzítik (1. ábra). Régóta ismert és alkalmazott, alacsony költségű módszer [34]. A vizsgálatok alapján a hajlítónyomaték maximuma pozitív korrelációt mutat a gyökérzet méretével, a gyökerek átmérőjével, valamint a korona kiterjedésének mértékével [36].…”
Section: Húzóvizsgálatunclassified